Optimalisasi Pelayanan Publik Di Kantor Desa Ukui Dua Kecamatan Ukui Kabupaten Pelalawan - Farhan Afriansyah (AMMA : Jurnal Pengabdian Masyarakat, 2023)
This research aims to describe and interpret the Optimization of Public Services at the Ukui Dua Village Office and its determinant factors at the Ukui Dua Village Office, Ukui District, Pelalawan Regency. The aim of this research is to find out how to optimize public services at the Ukui Dua Village Office, Ukui District, Pelalawan Regency. This research uses a naturalistic (qualitative) approach. The informants used as data sources were determined using purposive sampling and snowball sampling. Data collection techniques using interviews, observations and documents. Data analysis, namely interactive qualitative analysis with data analysis activities, namely data reduction, data display, and conclusion drawing/verification. The results of the research show that (1) Optimizing public services at the Ukui Dua Village Office regarding service procedures so that they are easier and simpler, namely by preparing SOPs for each activity or matter which contains the flow (start to finish, required conditions, completion time) in writing and can be easily read by the people served. Regarding the clarity and discipline of service officers, this is done by providing clearly the duties and functions of employees according to their position based on written job descriptions. For public services to be in accordance with the set time, cost and quality targets, this is done by following and adhering to the established SOPs and complying with the provisions regarding whether there is a policy of charging fees for the services provided, while services to the community are carried out by showing a friendly attitude, providing waiting room, seating/chairs for the public, even toilets, (2) The determining factors are the competency of service personnel, work motivation, work ethic and culture.